Vocalização dos cuidadores de ninho e os riscos de sobrevivência da prole em Malurus lamberti - Ottonicar, Rafael Gustavo Capinzaiki [UNESP] (2021)
Communication through sound is constant throughout the life of a bird, especially in breeding season when they use vocalizations to attract sexual partners, establish the boundaries of territories, alert of the presence of predators and assess nestling condition. This phenomenon becomes even more prominent in species that reproduce cooperatively, since organization and synchronization are necessary when more than two adults take care of a nest, and the voice is used as a mediator of this behavior. But this strategy has a cost: sound emission can increase adults and nest predation risk. Studies addressing this aspect have generally considered the vocalization produced by the young inside the nest, but not by the adults, in the context of caring for the offspring. The purpose of this study was, therefore, to identify the coexistent relationship between the degree of vocalization of adults of reproductive groups of the cooperatively breeding bird Malurus lamberti, and features of parental care such as length of permanence in the nest and rate of visits. Ultimately, we intended to evaluate the effects of this relationship on nest predation risk. We found that parental vocalizations do not affect nest predation risk. It is however, affected by predation risk. Depredated nests caring adults produced higher vocalization rates per visit in comparison to successful nests, which appears to be an outcome of the increased nest permanence time. This alone could be an indicator for nest predation risk.